2016
DOI: 10.4314/sajas.v46i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whey, molasses and exogenous enzymes on the ensiling characteristics, nutrient composition and aerobic stability of maize cobs

Abstract: The study was conducted to assess the effects of whey, molasses and exogenous enzymes on fermentation, aerobic stability and nutrient composition of ensiled maize cobs. Five treatments were ensiled in 1.5 L anaerobic glass jars over 32 days, namely i) control (maize cobs without additives (CON); ii) maize cobs with sugarcane molasses only (MOL); iii) MOL and whey (MOW); iv) MOW and exogenous enzyme at 0.5 g/kg maize cob mixture (ENZ1) and v) MOW and exogenous enzyme at 1 g/kg maize cob mixture (ENZ2). There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…Darby and Lauer (2002) reported a decrease in NDF content after ensiling, which is also similar to the report in this study. The increase in ADF content after fermentation is in contrast with the report of Kanengoni et al (2016) who reported that ensiling had reduced ADF content. The values obtained in this study in CP, TA, ADF and NDF contents were similar to the values obtained by Ballard et al (2001).…”
Section: Nutritional Composition Of the Foragecontrasting
confidence: 99%
See 1 more Smart Citation
“…Darby and Lauer (2002) reported a decrease in NDF content after ensiling, which is also similar to the report in this study. The increase in ADF content after fermentation is in contrast with the report of Kanengoni et al (2016) who reported that ensiling had reduced ADF content. The values obtained in this study in CP, TA, ADF and NDF contents were similar to the values obtained by Ballard et al (2001).…”
Section: Nutritional Composition Of the Foragecontrasting
confidence: 99%
“…It occupies a prominent position among the bulky organic manures available in India with a potential supply of 13.39 mt of N, P 2 O 5 and K 2 O per annum, besides improving the soil properties (Manna and Ganguly, 2003). The conjoint use of organic manures and chemical fertilizers (Xianjin et al, 2021, Lukiwati et al, 2018, Kanengoni et al, 2016 can help in enhancing and maintaining stability in production with least degradation in chemical and physical properties of soil. Supplementing N through organic sources plays a vital role in increasing the yield of any crop.…”
Section: Introductionmentioning
confidence: 99%
“…The crude protein level of the biofermented rice husk in the present research did not improve contrary to the expectation that addition of molasses which contain up to 44 g CP/kg DM (Xande et al, 2010) will rather improve the crude protein of the rice husk. A similar result was reported in the work of Kanengoni et al (2016). However, biofermentation treatment was able to reduce crude fiber from 59.20% which was the value of crude fiber in untreated rice husk to 37.34% crude fiber for biofermented rice husk.…”
Section: Proximate Compositionsupporting
confidence: 88%
“…However, Kanengoni,et. al.,(18) demonstrated that AS of the maize cobs deteriorated with the addition of molasses and enzymes with whey. Regarding effect of LW levels, results showed that higher (P<0.01) AS was observed in samples of DPL silages prepared with addition of LW at level of 1.5% as compared with those prepared without and with addition of LW at level of 1%.…”
Section: -Chatacteristics Of Silage Qualitymentioning
confidence: 99%
“…Similar results were obtained by Kanengoni,et. al.,(18) as a result of ensiling maize cobs and mango leaves with LW respectively. However, no effect was observed by Nkosi,et.…”
Section: -Chatacteristics Of Silage Qualitymentioning
confidence: 99%